Studi Kerusakan Jalan Piyungan - Wonosari dari Aspek Geoteknik - Agus Darmawan Adi (Forum Teknik, 2006)
Some  road  sections  in  Yogtakarta  sufer from  frequent damage following the  rainy  season. Repairs  have  been  conducted  regularly  and various  efforts  to  improve  the  road condition  have also  been  done,  however,  this  probletn  always comes  every  year.  Soil condition  below the  road pavement  is  suspected  to  give a  major  contribution  on road  damage  in  this  region.A series  of investigation  was carried  out  on  the  soil beneath the  road  of Piyungan-Wonosari section.  Field observation  on  road  damage condition  was  conducted  and  it  was followed by in situ  tests, consisting  of  hand  boring,  sampling and cone  penetration  test.  Properties  of soil were obtained from several  laboratory  tests.  To simulate  effect  of water  changes  on  soil  strength,  a series of shear strength  tests  were performed  on the  samples  made  of soil  with  various  water contents.The  results  indicate  that  the  road  damages in  this  region  are resulted by  several  reasons.  At road  section  built on slope, the  damage  was  mainly  caused  by downward  movement  of the Jill which  was not  rnassive  enough standing on  the  original  slope. Soil softening  due  to  water changes  is  identified  to give  a major contribution  on this  problem,  especially for road constructed  on clays.  Expansive  soil was  also found at  some  road  section.  This soil type produces  signiJicant  amount  of  pressure  and  volume changes  which lead  to movement  of  the adjacent  structures.Keywords  :  road-damage,  soil,  strength,  water,  soften